1985
DOI: 10.2486/indhealth.23.81
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exhaust pollutant sulfur dioxide on lipid metabolism of guinea pig organs.

Abstract: : Guinea pigs were exposed to exhaust pollutant sulfur dioxide (10 ppm) one hour daily for 30 days and the effect was studied on the lipid profiles of the liver, heart, lung and kidney.The liver exhibited depletion of phospholipids, cholesterol and C/P ratio, but ganglioside contents diminished. Elevated levels of cholesterol, C/P ratio, total lipids and phospholipids were discernible in the heart, and interestingly ganglioside concentration decreased.On the other hand, the lung showed increased concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In recent years, studies showed endogenous SO 2 pathways in tissues of rats including cardiovascular tissues [ 3 , 4 ]. The physiological effects of SO 2 were also confirmed, including vasodilation [ 4 – 6 ], negative regulation of cardiac function [ 7 ], and regulation of lipid metabolism [ 8 10 ]. Also, the pathophysiologic role of SO 2 in the processes of vascular structural remodeling (VSR) [ 11 , 12 ], inflammatory response [ 13 ], and oxidative response was indicated [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies showed endogenous SO 2 pathways in tissues of rats including cardiovascular tissues [ 3 , 4 ]. The physiological effects of SO 2 were also confirmed, including vasodilation [ 4 – 6 ], negative regulation of cardiac function [ 7 ], and regulation of lipid metabolism [ 8 10 ]. Also, the pathophysiologic role of SO 2 in the processes of vascular structural remodeling (VSR) [ 11 , 12 ], inflammatory response [ 13 ], and oxidative response was indicated [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur dioxide (SO 2 ) is a major toxic gas and environmental pollutant [1]. Its toxicity has been extensively investigated in humans, animals, and plants [2].…”
Section: Introductionmentioning
confidence: 99%
“…SO 2 was also found to have a negative inotropic effect as observed on isolated perfused rat heart, which in turn affects the heart rate and left ventricular developed pressure (Zhang and Meng, 2012 ). Besides in the cardiovascular system, SO 2 was also found to be involved in lipid metabolism, possibly due to its oxidant effect (Haider, 1985 ; Lovati et al, 1996 ). More interestingly, aligned with the well-known antimicrobial activity of SO 2 and its derivatives, Nojima and colleagues have demonstrated that sulfite is a neutrophil mediator of host defense that in vivo administration of lipopolysaccharide (LPS) would trigger sulfite release from neutrophil and increase serum sulfite concentration in rats (Mitsuhashi et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%